ANALISIS KUALITAS PELAYANAN PEGAWAI KLINIK HEWAN DI PROVINSI LAMPUNG - Lia Sari; Muhammad Ardiansyah (Universitas Bandar Lampung (UBL), 2023)
Within the scope of local government, public service can be interpreted as providing assistance or meeting the needs of individuals, groups, and other organizations with an interest in the organization, in accordance with established policies and guidelines. Since the main objective of public service is to satisfy service consumers, service principles are required for its implementation. In other words, entities providing public services are required to adhere to public service principles when providing public services. The research aims to find out how the quality of employee services at the Regional Technical Implementation Unit of the Animal Health Service Centre, Veterinary Public Health, and Veterinary Clinics This study uses a qualitative descriptive method; the data source in this study uses primary and secondary data. The data in this study were obtained based on employee informants of the Livestock and Health Service Office of Lampung Province. Data collection techniques in this study used interview techniques, documentation, and observation. The results of the study seen from the tangible and reliability dimensions are still not optimal. Lack of infrastructure, unavailability of operating rooms and operational support drugs, unavailability of separate examination rooms, unavailability of facilities and infrastructure for handling clinical waste, and a limited number of personnel with the required competencies and expertise from the dimensions of responsiveness, assurance, and empathy, the service quality of veterinary clinic officers is good. Officers are able to provide services carefully, precisely, and quickly. Officers work professionally in accordance with existing standard operating procedures. In general, the service quality of veterinary clinic officers is good but not optimal.